(untitled) (International Journal of Engineering and Computer Science, 2025)
With the increasing factors of stress in workplaces, migration for work opportunities, and loss of communication with family members or friends, people tend to isolate themselves, and due to the loneliness of the individual, negative factors tend to harm their own lives as well as their loved ones. In this study, an application is designed to stimulate human touch when pressed on specific points on their mobile device, therefore making physical contact with their loved one away from them. The application is designed as a nine button array. When a button is pressed, a specific emotional effect is transferred to the other side using nine servo motors, creating patterns of vibration. The servo motors integrated into the mobile phone’s back side, which could be easily held and handled. The effectiveness of the developed system was tested through a subjective evaluation. As a result, not only subject can distinguish emotional icons, but also can transfer their emotional thoughts to tactile icons.